Early Impacts of COVID-19 on Nutrition Intake and Household Dietary Diversity in Kupang District, East Nusa Tenggara, Indonesia - Juntra Utama, Lalu; Yunita, Lina; Sembiring, Anita Christina; Da Costa, Santa Luciana; Nur, Astuti; Abdi, Lalu Khairul; Suhaema, Suhaema (Global Medical & Health Communication (GMHC), 2023)
One of the social problems solving the direct impact on the community is overcoming household food security due to the COVID-19 pandemic. This study aims to analyze household food security during the COVID-19 pandemic and link it to the nutrient intake and nutritional status of children under five in the Kupang district area. This cross-sectional study is based on a survey conducted on the Timorese population in Kupang, East Nusa Tenggara, Indonesia, from May to October 2021. Data on household dietary diversity was collected through the 24-hour food recall using the household dietary diversity score (HDDS). The study sample was taken from Timorese population families with toddlers under five years, and 1,444 families voluntarily participated in this study. Subjects were taken at each public health using a simple random method. This study analyzes the Spearman correlation test with the HDDS and the proportion of food expenditure. A 63% of households had a balance of less cost (<50%) with an average of 63.9. Generally, households (90.4%) had a pretty good diet diversity score. Food groups that were relatively highly consumed by most households included cereals (100%), sugar and sweeteners (90.2%), oils and fats (93.7%), seasonings, and spices (89.4%). A significant effect with p<0.05 was on HDDS during the COVID-19 pandemic. The food consumption score is another indicator widely used in determining household food security. Therefore, it is necessary to revalidate tests in further studies of these indicators.